France in the International Relations of the Russian Empire in 1815-1825 - Goncharenko, Lesya; Evsyukova, Yana (Traektorii͡a︡ nauki : mezhdunarodnyĭ ėlektronnyĭ nauchnyĭ zhurnal, 2017)
The article studies the role and place of France in the international relations of Russia in 1815-1825. It characterizes the interdependence of the two players of international policy in cooperation in various areas. The influence of France on the international position of the Russian Empire is studied out. The positions of various groups in the middle of the Russian ruling circles, concerning the issue of development and implementation of international relations with France in 1815-1825 are highlighted. У статті досліджено роль та місце Франції в міжнародних відносинах Росії у 1815–1825 рр. Охарактеризовані причині взаємозалежності двох гравців міжнародної політики у співпраці в різних напрямках. З’ясовано вплив Франції на міжнародне становище Російської імперії. Висвітлені позиції різних угрупувань у середині російських правлячих кіл у питанні розробки та реалізації міждержавних відносин щодо Франції у 1815–1825 рр.